From Cherry Picking to R1vasc, Clusters, and Compass Points: Evolution, Technique, and Results of Parenchymal-sparing One Stage Hepatectomy for Multiple Colorectal Liver Metastases - Torzilli, Guido; Milana, Flavio; Perano, Vittoria; Calafiore, Eleonora; Galvanin, Jacopo; Costa, Guido; Cimino, Matteo; Palmisano, Angela; Del Fabbro, Daniele; Donadon, Matteo; Procopio, Fabio (Annals of surgery, 2025)
Evaluate the technical development and long-term outcomes of Parenchymal-sparing One-Stage Hepatectomy (POSH) for colorectal liver metastases (CLM). For multiple bilobar CLM, 2-stage hepatectomy (TSH) is suggested, with liver transplant proposed for unresectable cases. In this context, POSH showed effectiveness. A prospective cohort of patients with ≥4 bilobar CLM (2004-2023) was analyzed using an intention-to-treat approach. POSH patients were classified by surgical margin. The primary endpoint was the technique evolution in terms of complexity, feasibility, and indications; secondary endpoints included POSH oncological validity, safety, and survival. Of 407 patients, 388 underwent POSH, and 17 TSH. Resection area-to-tumor number ratio improved from 0.67 (2004-2007) to 0.41 (2020-2023, P =0.024), eliminating TSH after 207 POSH cases. Among POSH cases: 105 (27.4%) were R0, 153 (39.9%) R1p (tumor-parenchymal exposure), 37 (9.7%) R1v (tumor-vessel detachment), and 88 (23.0%) R1vp (vascular/parenchymal exposure). R1v had outcomes comparable to R0, while R1p had worse OS, RFS, and local recurrence ( P <0.05). R1vp showed intermediate outcomes. Tumor size (HR 1.071, P =0.002), primary tumor nodal status (HR 1.695, P =0.005), and R1p margin (HR 1.481, P =0.024) predicted OS. Major complications occurred in 9.3%, 90-day mortality was 0.8%. Redo-hepatectomy was feasible in 93 of 122 (76.2%) patients with intrahepatic recurrence, providing a significant 5-year OS benefit. POSH is effective for bilobar CLM. Advancements in tumor clustering eliminated the need for TSH even in complex cases. R1v outcomes confirm the validity of vascular detachment.